A comprehensive review of glycocalyx investigation and therapeutic applications in sepsis and septic shock - Muntean Anastasia; Ambros Ala; Cojocari Sergiu; Maximciuc Ștefan; Cumpătă Serghei (Romanian Journal of Laboratory Medicine)
Sepsis is a global health challenge that causes more than 11 million deaths annually and represents a substantial medical and economic burden. With rising treatment costs and significant mortality rates associated with organ dysfunction and septic shock, research efforts have focused on investigating the mechanism of glycocalyx (GCX) degradation as well as its regenerative capacity. Therefore, GCX has become a target in therapeutic strategies.